Moral Character and Virtue in Anime: An Aristotelian Reading of Wind Breaker Season 2 Episode 10 - Fanani, Ahmad Farid (Asian Journal of Media and Communication, 2025)
The rise of social apathy in modern society reflects a deeper moral disconnection that calls for renewed ways of engaging with ethical reflection. This study examines how Wind Breaker Anime Season 2 Episode 10 represents Aristotelian virtue ethics as a narrative form of moral imagination within popular culture. Rather than assessing audience impact, this study highlights the representational potential of anime as a medium that recontextualizes classical virtue ethics within modern moral discourse. Employing a qualitative content analysis, the research explores how arete (moral excellence), phronesis (practical wisdom), and eudaimonia (flourishing) are expressed through the characters’ actions and emotional transformations, particularly those of Suzurin. The episode’s portrayal of apology, empathy, forgiveness, and self-acceptance reflects Aristotle’s doctrine of the golden mean and the process of moral habituation, while collective support and the granting of second chances manifest justice and friendship (philia) in a social context. The findings suggest that Wind Breaker articulates the moral possibilities of virtue ethics within contemporary youth narratives, illustrating how classical ethical concepts can be reinterpreted through visual storytelling.